Processing of Red Velvet Cake Using Natural Dyes of Red Bitter Fruit (Beta Vulgaris) And Red Spinach (Amaranthus Tricolor Linn) - Anita Wulandari; Wahyu Kanti Dwi Cahyani; Pongky Lubas Wahyudi (Faculty of Agriculture, Merdeka University Surabaya, 2021)
The red velvet that many people like is a pastry food that is usually found in restaurants and cafes. Red Velvet, which usually uses red food coloring, in this study replaced it with red beet and spinach coloring. Beets, which have high nutrition, are very useful and suitable to be processed into natural dyes in the home industry that are easy to process. One of the products to apply it is Red Velvet cake. Red Velvet cake basically uses a mixture of food coloring. This research tries to replace red food coloring by utilizing beet and red spinach which are very good for the body. This study aims to provide a new alternative to natural dyes in the making of Red Velvet cake. Experimental research was carried out by conducting systematic and planned experiments and tests on Red Velvet cake and collecting primary and secondary data as well. All data were presented descriptively with SPSS. From the mean results, it can be concluded that the Red Velvet Cake using red beet and red spinach dye is acceptable to the public.